If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y * 27 = 5y Reorder the terms for easier multiplication: 2 * 27y = 5y Multiply 2 * 27 54y = 5y Solving 54y = 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 54y + -5y = 5y + -5y Combine like terms: 54y + -5y = 49y 49y = 5y + -5y Combine like terms: 5y + -5y = 0 49y = 0 Divide each side by '49'. y = 0 Simplifying y = 0
| 60y-4=173 | | n^2-16n-24=-8 | | 2.3x+34.7=3.8-8.0x | | 7c=2v-20 | | 6x+24+2=-4+-28 | | 5x-8=5y | | (x+5)(x-18)=0 | | -2[4-(3b+2)]=4-2(3b+9) | | 48-31w=-18 | | x+2x+x+3=30 | | 6x+2x+x+3= | | w^2-13w-36=0 | | 4-3x=42 | | 22(2x+y)=29 | | w=.28w+48 | | 2/3x-0,7=1,3x+2 | | -3125=r^5 | | 6x^2+9x-36=0 | | 6x+=20 | | 5sinx+4=3sinx+3 | | f(x)=2x^2+16x+5 | | 3(x-1)+6=-6x(x+7) | | 5(2w-7)=65 | | -4x+3y+15=0 | | 7x-92=252 | | T+10=7t-13 | | -8+2v=-22 | | 2y+2=-4 | | 4(3x+2)=7x+5 | | (-4m+5)(3m-6)=0 | | 95=5(-7x-9) | | -10=2v+4 |